Development of a High-Resolution Melting Method for the Detection of Clarithromycin-Resistant Helicobacter pylori in the Gastric Microbiome - Zupeng Kuang; Huishu Huang; Ling Chen; Yanyan Shang; Shixuan Huang; Jun Liu; Jianhui Chen; Xinqiang Xie; Moutong Chen; Lei Wu; He Gao; Hui Zhao; et al. (MDPI AG, 2024)
Background: The issue of Helicobacter pylori (H. pylori) resistance to clarithromycin (CLR) has consistently posed challenges for clinical treatment. Hence, a rapid susceptibility testing (AST) method urgently needs to be developed. Methods: In the present study, 35 isolates of H. pylori were isolated from 203 gastritis patients of the Guangzhou cohort, and the antimicrobial resistance phenotypes were associated with their genomes to analyze the relevant mutations. Based on these mutations, a rapid detection system utilizing high-resolution melting (HRM) curve analysis was designed and verified by the Shenzhen cohort, which consisted of 38 H. pylori strains. Results: Genomic analysis identified the mutation of the 2143 allele from A to G (A2143G) of 23S rRNA as the most relevant mutation with CLR resistance (p < 0.01). In the HRM system, the wild-type H. pylori showed a melting temperature (Tm) of 79.28 ± 0.01 °C, while the mutant type exhibited a Tm of 79.96 ± 0.01 °C. These differences enabled a rapid distinction between two types of H. pylori (p < 0.01). Verification examinations showed that this system could detect target DNA as low as 0.005 ng/μL in samples without being affected by other gastric microorganisms. The method also showed a good performance in the Shenzhen validation cohort, with 81.58% accuracy, and 100% specificity. Conclusions: We have developed an HRM system that can accurately and quickly detect CLR resistance in H. pylori. This method can be directly used for the detection of gastric microbiota samples and provides a new benchmark for the simple detection of H. pylori resistance.